Qualitative Interpretation of Total Magnetic Field Anomaly Data Reduction Transfprmation to The Poles in Weh Island - Kendek Limbong; nazli ismail; Gunawati Gunawati (PSI-Aceh, 2018)
Telah dilakukan penelitian menggunakan metode magnetik di Pulau Weh, Provinsi Aceh. Data medan magnetik total diukur menggunakan instrumen Proton Precission Magnetometer (PPM). Titik pengukuran berjumlah 195 yang meliputi Pulau Weh. Data medan magnetik total selanjutnya dilakukan koreksi diurnal dan koreksi International Geomagnetic Reference Field (IGRF) untuk menghasilkan data intensitas anomali medan magnetik total. Data anomali medan magnetik total selanjutnya ditransformasi reduksi ke kutub. Pola kontur intensitas anomali medan magnetik total hasil transformasi reduksi ke kutub digunakan untuk mengidentifikasi struktur bawah permukaan Pulau Weh. Pola kontur intensitas anomali medan magnetik total hasil reduksi ke kutub memiliki kesesuaian dengan peta pola kelurusan Sesar Sumatera di Pulau Weh. Arah pola kontur intensitas anomali medan magnetik total hasil reduksi ke kutub juga memiliki kesesuaian dengan arah patahan-patahan yang ada di Pulau Weh.Survey of magnetic method has been done in Weh Island, Aceh Province. Total magnetic field data were acquired using Proton Precision Magnetometer instrument. 195 stations were measured on the Weh Island that cover about 156,3 km2. The total magnetic field data were corrected by diurnal and International Geomagnetic Reference Field corrections in order to obtain total magnetic field anomaly data. The total magnetic field anomaly data were transformed to the pole since the data were measured at low lattitude geomagnetic area. The contour patterns of the total magnetic field anomaly reduced to the pole were used to identify the Weh Island's subsurface structures. The contour patterns are in agreement with the map of the Sumatera Fault on Weh Island. Both maps show NW-SE structures dominated the area those are corresponded to the local faults. Keywords: magnetic method, field anomaly intensity, pole, contour patterns, Weh IslandDaftar Pustaka Blakely, Richard J. 1996. Potential Theory In Gravity and Magnetic Applications. Cambridge University Press, Cambridge.Dirasutisna, S dan Hasan A. R. 2005. Geologi Panas Bumi Jaboi, Sabang, Provinsi Aceh Nanggroe Darussalam. Pemaparan Hasil Kegiatan Lapangan Subdit Panas Bumi 2005. Indonesia, Volume. 1: 1-6.Fernandez-Blanco, David, Philippon, Melody, von Hagke, Christoph. 2016. Structure and kinematics of the Sumatran Fault System in North Sumatra (Indonesia), Tectonophysics, doi: 10.1016/j.tecto.2016.04.050.Howell, L. E. 2010. Characterizing shallow intrasedimentary faults using magnetic depth estimation methods: Preliminary results of a high-resolution aeromagnetic survey at the San Luis Basin, south-central Colorado. Thesis. Bachelor of Arts degree from Carleton College, Minnesota.Indratmoko, P., Nurwidyanto M. I., dan Yulianto T. 2009. Interpretasi Bawah Permukaan Daerah Manifestasi Panas Bumi Parang Tritis Kabupaten Bantul DIY dengan Metode Magnetik. Jurnal Berkala Fisika. Vol. 12, No. 4 (1410–9662): 153-160.Jain, Sudhir. 1988. Total Magnetic Field Reduction –The Pole or Equator? A Model Study. Canadian Journal of Exploration Geophysics, Vol. 24 No. 2: 185-192.Rahmad, B dan Ilahude, D. 2011. Pola Anomali Magnet dan Nilai Susceptibilitas dari Batuan Dasar Pada Pemetaan Geologi dan Geofisika di Perairan Teluk Bone Sulawesi Selatan. Jurnal Geologi Kelautan. Vol. 9. No. 13: 13-22.Telford, W. M., Geldart L. P. Dan Sheriff R. E. 1990. Applied Geophysics Second Edition. Cambridge University Press, Cambridge.